Epidemiology of Canine Keratoconjunctivitis Sicca and the Efficacy of Cyclosporine and Tacrolimus in its Clinical Management and Tear Production: A Comparative Study - Bhalodi, Apeksha S; Patel, Abhi S; Saripadiya, Bhautik N; Patel, Abhishek K; Mecvan, Arnold R; Mayani, Ankush J; Parikh, Pinesh V (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Keratoconjunctivitis sicca (KCS) or dry eye is a significant cause of ocular morbidity in dogs. This study was aimed to determine the incidence of KCS and to compare the therapeutic efficacy of oil-based 2% cyclosporine and 0.03% tacrolimus ointment. Over a period of one-year, KCS was the most frequently diagnosed ophthalmic condition (24.70%, 41/166) among canine ocular affections. Incidence of KCS was the highest in dogs aged 1-5 years (65.85%), in females (58.54%), and in the Pug breed (43.90%). For the therapeutic trial, 26 client-owned dogs (52 eyes) were divided into two treatment groups: cyclosporine and tacrolimus and monitored for 60 days. The key clinical parameters, viz., ocular discharge, conjunctival hyperaemia, corneal pigmentation and Schirmer tear test (STT) values were systematically scored. Both treatments significantly mitigated the inflammatory signs of ocular discharge and conjunctival hyperaemia (p<0.05). Treatment with tacrolimus successfully arrested the advancement of pigmentation, particularly in mild KCS cases, showing a statistically significant (p<0.05) advantage over 2% cyclosporine. 0.03% tacrolimus was also found to be significantly superior (p<0.05) to 2% cyclosporine in increasing STT values across all severity groups (mild, moderate, and severe) by day 60. In severe KCS cases, only tacrolimus produced a statistically significant increase in tear production. These findings underscores that while both agents address superficial inflammation, tacrolimus has a superior lacrimostimulant effect providing a superior therapeutic outcome by controlling the vision-threatening progression of corneal pigmentation for the management of canine KCS.